2019
DOI: 10.1111/phn.12599
|View full text |Cite
|
Sign up to set email alerts
|

When reach exceeds touch: Student experiences in a cross‐sector community‐based academic‐practice partnership

Abstract: Objective: A partnership between three nursing programs, multiple high-needs public school districts and a local asthma coalition was developed as a way to build shared capacity aimed at improving health outcomes for children with asthma. This article explores student perceptions of their clinical experiences teaching asthma self-management within a regional cross-sector, community-based, multi-site academic-practice partnership. Design: Nursing faculty from three Long Island, New York-based nursing programs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Third, there has been a recent increase in the incorporation of self-reflection into public health curriculum and programs through various reflective formats like journal, focus group discussion, photovoice, and narrative reflective practice (Sendall and Domocol, 2013;Hoffman and Silverberg, 2015;Babenko-Mould et al, 2016;Adams, 2019;Janssen Breen et al, 2019;Andina-Díaz, 2020;Haffejee, 2021). While Artioli et al (2021) conducted qualitative meta-synthesis on the use of reflective writing on health professionals, focusing on one type of reflection format is insufficient to determine the impacts of self-reflection in public health higher education.…”
Section: Gaps In Literature On Self-reflection In Higher Educationmentioning
confidence: 99%
See 2 more Smart Citations
“…Third, there has been a recent increase in the incorporation of self-reflection into public health curriculum and programs through various reflective formats like journal, focus group discussion, photovoice, and narrative reflective practice (Sendall and Domocol, 2013;Hoffman and Silverberg, 2015;Babenko-Mould et al, 2016;Adams, 2019;Janssen Breen et al, 2019;Andina-Díaz, 2020;Haffejee, 2021). While Artioli et al (2021) conducted qualitative meta-synthesis on the use of reflective writing on health professionals, focusing on one type of reflection format is insufficient to determine the impacts of self-reflection in public health higher education.…”
Section: Gaps In Literature On Self-reflection In Higher Educationmentioning
confidence: 99%
“…After reading the remaining 68 articles, 14 were not relevant to selfreflection, 11 did not include evaluation results, five did not meet the target population criteria, and we were unable to isolate the results of undergraduate from the graduate population in four studies. The remaining 34 studies were included in our systematic review (Schaffer et al, 2005;Champagne, 2006;Brondani, 2010;Carroll and Mccarthy, 2010;Shepherd, 2010;Lee et al, 2011;Solomon and Risdon, 2011;Leipert and Anderson, 2012;Fortugno et al, 2013;Sendall and Domocol, 2013;Koh et al, 2014;Lencucha, 2014;Oakes and Sheehan, 2014;Stefaniak and Lucia, 2014;Hoffman and Silverberg, 2015;Karlsen et al, 2015;Krumwiede et al, 2015;McKay and Dunn, 2015;Babenko-Mould et al, 2016;Olson and Burns, 2016;Dundas et al, 2017;Padykula, 2017;Rooks and Holliman, 2018;Adams, 2019;Burnett and Akerson, 2019;Harver et al, 2019;Janssen Breen et al, 2019;Njoku and Ferris State University, 2019;Andina-Díaz, 2020;Chang and Chen, 2020;Harrison et al, 2020;Sambell et al, 2020;Suwanbamrung and Kaewsawat, 2020;Haffejee, 2021). Of the 34 studies, 29 reported qualitative evaluation results, and five reported mixed methods evaluation results.…”
Section: Descriptive Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Students learn the application and necessity of implementing EBP as a part of daily patient care (Phillips et al, 2019). Moreover Breen et al (2019) found that students immersed in an APP experience developed an appreciation and respect for the contributions of peers and the work of school nurses in addressing asthma self-management for children. They acquired collaboration skills, assumed collaboration roles, and became empathetic toward the social and environmental plight of these families.…”
Section: Liter Ature Re Vie Wmentioning
confidence: 99%